Grain Configuration Effect on Pore Water Pressure in Debris Flow - Yang, Taiqiang; Liu, Daochuan; Li, Yong; Guo, Xiaojun; Zhang, Jun; Jiang, Yu (Frontiers in Earth Science, 2021)
The generation and development of excess pore water pressure directly affects the interaction between debris flow grains, which can significantly reduce the friction strength and promote the movement of debris flow. It has been found that coarse grains may favor the increase in excess pore water pressure in the debris flow, but the effect due to grain configuration is missing in studies. In order to study the influence of grain configuration, field investigations and laboratory tests were carried out for two typical grain configuration in debris flow, i.e. flow with coarse grains evenly mixed (case II) and flow with coarse grains float on the surface (case Ⅲ) and. The results show that case Ⅲ generates much higher excess pore water pressure than case II. The variation of relative excess pore water pressure (Ur) with time (t) satisfies the power function relationship: Ur=mt-n, the power exponent n reflects the decaying rate of Ur, that is, the smaller the value is, the slower the decaying is. Compared with other cases, in case Ⅲ, it often has a smaller n value, that is, the dissipation rate of excess pore water pressure is slower. This study is helpful to better understand the influence of coarse grains and grain separation on pore water pressure and to understand the granular effect in the process of debris flow movement.